Employment Challenges in the Second Wave of the COVID-19 Virus from a Corporate Perspective - Barbara, Pirohov-Tóth (International Journal of Engineering and Management Sciences, 2021)
The changed market conditions caused by the Covid-19 virus forced companies to rethink their strategy and structure and to optimize their processes. The aim of my research is to shed light on the changes in the second wave of the coronavirus epidemic that have had a significant impact on the operation of businesses and presented them with significant challenges. For the study, I used the results of a previous questionnaire survey (Pirohov-Tóth 2020; Pirohov-Tóth, Kiss 2021), which were supplemented with a literature analysis and statistical data from the database of the Central Statistical Office. Furthermore, compared to the first wave of the virus, I examined how job productivity changed in the second wave of the virus. Finally, corporate crisis management options have been presented in my analysis, the practical application of which can contribute to re-emerging from the crisis. It can be stated that the acceleration of digitization and the widespread expansion of advanced technological tools and methods can be considered as one of the biggest positives of the viral situation, which can also mean survival for companies in this pandemic situation.